Portraits of Paul's Performance in the Book of Acts Luke's Apologetic Strategy in the Depiction of Paul as Messenger of God - den Heijer, Arco (Mohr Siebeck, 2021)
In the Book of Acts, Paul is portrayed as a messenger who brings the good news of God to the world. He is a commanding orator who captivates his audiences, including a Roman senatorial proconsul and a Jewish king, with his gestures, appearance, and speeches. His performances appeal to both Greco-Roman and Jewish cultural scripts alike. But why does Luke portray Paul in this way? Using insights from both modern performance studies and ancient rhetoric, Arco den Heijer analyses five episodes from Acts (in Paphos, Pisidian Antioch, Lystra, Athens, and before Agrippa in Caesarea) to suggest that Luke's portraits of Paul's performance served to counter negative views of Christians in both Roman and Jewish circles, views that circulated in the social network of Theophilus, the addressee of the book.